2020
DOI: 10.3389/fmolb.2020.00205
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair and Signaling in Immune-Related Cancer Therapy

Abstract: Cancer therapy using immune checkpoint inhibitors (ICIs) is a promising clinical strategy for patients with multiple types of cancer. The expression of programmed cell death ligand-1 (PD-L1), an immune-suppressor ligand, in cancer cells is a factor that influences the efficacy of ICI therapy, particularly in the anti-programmed cell death protein-1 (PD-1)/PD-L1 antibody therapy. PD-L1 expression in cancer cells are associated with tumor mutation burden including microsatellite instability because the accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 74 publications
(81 reference statements)
1
28
0
Order By: Relevance
“…The predictive role of TMB in ICI treatment has been confirmed in many clinical studies (Davoli et al, 2017). Tumor cells with high TMB can produce more tumor-specific antigens and thus can be easily recognized and killed by immune cells (Kakoti et al, 2020). In our OS model, the TMB of the low-risk group was higher and the prognosis of the high-TMB group was remarkably better after the samples were grouped according to TMB.…”
Section: Discussionsupporting
confidence: 56%
“…The predictive role of TMB in ICI treatment has been confirmed in many clinical studies (Davoli et al, 2017). Tumor cells with high TMB can produce more tumor-specific antigens and thus can be easily recognized and killed by immune cells (Kakoti et al, 2020). In our OS model, the TMB of the low-risk group was higher and the prognosis of the high-TMB group was remarkably better after the samples were grouped according to TMB.…”
Section: Discussionsupporting
confidence: 56%
“…Studies by Singavi and others have suggested that the amplification of some genes on the human chromosome 11q13, such as CCND1, FGF3, FGF4, and FGF19, may be related to the occurrence of hyper-progression (11). The loss of function of the ATM is related to the autosomal recessive disease ataxia-telangiectasia, hypersensitivity to ionizing radiation, cancer susceptibility, immunodeficiency, and genomic instability, which may indicate better immune efficacy and sensitivity to ionizing radiation (12,13). The loss of PBRM1 may change the overall tumor cell expression profile.…”
Section: Discussionmentioning
confidence: 99%
“…PARP inhibitors can enhance sensitivity in the tumor microenvironment to ICB through a variety of mechanisms including increased chromosomal aberrations due to deficiency in DNA repair pathways, and modulation of immune response in the tumor microenvironment ( Teo et al 2018 ; Chabanon et al 2019 ). In addition, the presence of HRD in cancer cells as well as the use of PARP inhibitor–induced synthetic lethality could lead to neoantigen formation that may resensitize tumor cells to ICB ( Kakoti et al 2020 ).…”
Section: Discussion: Combination Checkpoint Inhibitors and Parp Inhibitors In The Treatment Of Melanoma With Detected Hrdmentioning
confidence: 99%